Diagnostic Utility of Haematologic Scoring System in Neonatal Sepsis - Modali Rishita Sarma; Jinkala Sree Rekha; Srikanta Kanungo (JCDR Research and Publications Pvt. Ltd., 2019)
Introduction: Sepsis is an important cause of neonatal mortality and morbidity. Numerous serological markers exist for diagnosis of sepsis which acts as adjuvants to the clinical signs. A Haematological Scoring System (HSS) for predicting sepsis in neonates which includes the total leucocyte count, immature neutrophil count, toxic changes in the neutrophils and various other parameters in the routine haemogram was used. Aim: In the present study, authors evaluated the diagnostic utility of HSS in predicting neonatal sepsis in neonates admitted with clinical diagnosis/suspicion of sepsis. Materials and Methods: This was a prospective observational study, conducted on neonates with clinical diagnosis/suspicion of sepsis. The various parameters included in the HSS for neonatal sepsis were analysed in all the smears. Statistical analyses were conducted; the sensitivity, specificity, Positive Predictive Value (PPV) and Negative Predictive Value (NPV) of each variable of HSS score was calculated. The comparison of HSS score between the culture positive sepsis and culture negative sepsis was carried out by using Independent t-test or Mann-Whitney U test. Results: Seventy-eight samples were received from neonates with clinical diagnosis/ suspicion of neonatal sepsis. Among the variables in HSS score, Total Neutrophil Count (TNC) and Immature Neutrophil Count (INC) show high sensitivity; Immature to Mature neutrophil ratio (I:M ratio) and low platelet count showed high specificity; TNC and INC showed high PPV; toxic change and low platelet count showed high NPV in predicting neonatal sepsis. Presence of Schistocytes in the peripheral smear showed high specificity of 80% in predicting neonatal sepsis. Increased band count has a high specificity (91%) and NPV (72%) in predicting neonatal sepsis. Conclusion: HSS score had high sensitivity and NPV of 91% in predicting neonatal sepsis. The prevalence rate ratio of neonates developing sepsis with high HSS score is 3.9 times more compared with neonates with low HSS score. HSS is a simple, quick, cost-effective and routine laboratory test which helps in predicting neonatal sepsis. The higher the HSS score, more is the probability of neonatal sepsis.